Metastatic insulinoma: exploration from clinicopathological signatures and genetic characteristics - Zhang, Jingcheng; Jiang, Rui; Hong, Xiafei; Wu, Huanwen; Han, Xianlin; Wu, Wenming (Frontiers in Oncology, 2023)
Abstract Background: Insulinoma is a rare type of pancreatic neuroendocrine tumor with low incidence and low-malignant features. While very few insulinomas present with malignant behaviours, such as lymph node and liver metastasis, only a few studies have focused on this field owing to the limitation of samples. Existing evidence suggests that metastatic insulinoma largely derive from non-functional pancreatic neuroendocrine tumor. However, we found a portion of metastatic insulinomas may derive from non-metastatic insulinomas and explored their clinicopathological signatures and genetic characteristics. Methods: Four metastatic insulinoma patients with synchronous liver metastasis or lymph node metastasis at the Peking Union Medical College Hospital between October 2016 and December 2018 were enrolled, and whole exon and genome sequencing were performed on fresh frozen tissues and peripheral blood samples. Clinicopathological information and genomic sequencing results were collected and matched to explore the characteristics of the metastatic insulinomas. Results: These four metastatic insulinoma patients underwent surgery or interventional therapy, and their blood glucose levels immediately increased and maintained within standard range after treatment. For these four patients, the proinsulin/insulin molar ratio <1 and primary tumors were all present as PDX1+, ARX-, and insulin+, which were similar to non-metastatic insulinomas. However, the liver metastasis showed PDX1+ and ARX+, insulin+. Meanwhile, genomic sequencing data showed no recurrently mutations and typical CNV patterns. However, one patient harboured the YY1 T372R mutation, a recurrently mutated gene in non-metastatic insulinomas. Conclusions: A portion of metastatic insulinomas were largely derived from non-metastatic insulinomas in hormone secretion and ARX/PDX1 expression patterns. Meanwhile, the accumulation of ARX expression may be involved in the progression of metastatic insulinomas.